Band-tunable photodetectors based on graphene/alloyed ZnxCd1−xS film hybrids. Issue 8 (16th January 2017) - Huang, Fan; Ouyang, Sheng; Jia, Feixiang; Cai, Caoyuan; Xu, Zhihao; Wu, Congjun; Ma, Yang; Wang, Min
Abstract : We have achieved band-tunable photodetectors based on graphene/alloyed Zn x Cd1– x S film hybrids with cut-off edge in spectra response gradually changed from 410 nm to 580 nm. Abstract : Graphene/semiconductor film hybrid-based photodetectors have attracted extensive attention because of their ultra-high performance. However, only the photoconductive behavior of binary semiconductors with fixed bandgap was studied since achieving tunable optoelectronic properties is significant for the practical applications of semiconductors. Herein, alloyed Zn x Cd1− x S (0 ≤ x ≤ 1) films with complete compositional tunability were successfully prepared by an e-beam evaporation method via changing the molar ratio of ZnS to CdS in the target. UV-visible optical absorption measurements showed that the composition-dependent band-edge absorption is generated in the as-prepared alloyed Zn x Cd1− x S films, with the energy gaps continuously shifted from 2.41 eV ( x = 0, CdS) to 3.67 eV ( x = 1, ZnS). After graphene is transferred on the alloyed Zn x Cd1− x S films, band-tunable photodetectors are achieved based on graphene/alloyed Zn x Cd1− x S film hybrids with the cut-off wavelength in the spectral response gradually changing from 410 nm to 580 nm. Obviously, the method introduced in this study can be extended to fabricate other graphene/alloyed ternary film hybrid-based photodetectors with band tunability in the visible and infrared region.